Green Skills in the European Labour Markets - Karachalios, George; Kotsios, Vaios (HAPSc Policy Briefs Series, 2023)
This paper aims at exploring the significance of green skills in the European labour market, highlighting their importance for workers in various occupations and fields of the European economy. The European labour market has undergone several significant changes over the past decade as a result of the increased demand for sustainable practices and the need for a green transition. New strategies and policies have lavishly evolved to address the challenges related to climate change and environmental decay. The concept of green skills has thus emerged, referring to the skills, knowledge and competences required for working in a sustainable and environmentally friendly way. In this context, this paper analyses specific aspects of the economic, environmental, and social impact of green skills from the point of view of an increasing demand for green skills in various occupations. It finally examines the benefits of having a well-trained workforce equipped with green skills as well as the level of responsiveness for certain EU member states towards the need to address existential challenges of the green transition.